Ecological Affinity: Exploration into the Romantic Construction of Ecology in Devkota’s Poetry - Nepal, Guna Raj (Bodhi: An Interdisciplinary Journal, 2025)
This article explores the romantic construction of ecology in the poetic works of modern Nepali poet Laxmi Prasad Devkota. It uses ecocriticism as its theoretical framing to recognize and capitalize on the ecological undertones ingrained in his romantic poetry. This framing situates the poet’s romantic imagining within the relevant literature and attempts to find a dialogic space to study his intellectual orientation toward the holistic understanding of the natural world as conceptualized in ecocriticism. The study also explores the entrenched ecological ideas reflected in three deliberately chosen poetic works: Jwarsamana Prakriti, Muna Madan, and Shakuntala. In so doing, it attempts to capture how these selected texts display a subtle congruence in shaping Devkota’s ecological insights despite their explicit differences in length and scope. The findings of this study reveal how the nature-women relationship, the animal world, and the green language coalesce the construct of his romantic ecology. Additionally, the study points out its limitations and offers some implications for revisiting Devkota’s poetic works through the ecocritical lens.